RESILIENSI EKONOMI PESANTREN MELALUI HOLDING BISNIS HEBITREN: APLIKASI ASSET BASED COMMUNITY DEVELOPMENT - Ali, Jeihan Azhar; Tri Pambekti, Galuh; Baroroh, Hilmy; Hassany, Egha Ezhar Junaeka Putra; Insani Saibil, Defi (DEVOSI, 2024)
Pesantren is a religious institution that is one of the drivers in the fields of populist economy, MSMEs, and sharia economy, which has potential, especially in the midst of the COVID-19 pandemic. The economic resilience of pesantren is very crucial in the ongoing ecosystem of the pesantren economy. The development of pesantren in responding to the economy has motivated Bank Indonesia to form the Pesantren Economics and Business Association (HEBITREN), especially the Yogyakarta regional office in 2021. The formation of HEBITREN requires contributions from other institutions, especially educational institutions in transforming business model ideas and ideas for business holding between pesantren. The benefits of this service for pesantren administrators are the receipt of input or transfer of knowledge related to the preparation of the Hebitren business model, business planning and RAPB, preparation of standard operating procedures, financial reports, organizational structure and job descriptions, mapping prospective Hebitren managers, and the core business to be run. The study center for the empowerment and economic development of pesantren, UIN Sunan Kalijaga, was present as a companion to HEBITREN in realizing the economic resilience of pesantren through the HEBITREN business holding by applying Asset Based Community Development. The output of this agenda is in the form of a Hebitren business model, business planning and RAPB, preparation of standard operating procedures, financial reports, organizational structure and job descriptions, mapping of prospective Hebitren managers, and the core business to be run.